PENGEMBANGAN MEDIA E-KOMPAS (ELEKTRONIK KOMIK IPAS) MATERI WUJUD ZAT DAN PERUBAHANNYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK KELAS IV SD - Juwita Kumala Sari Anne; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop E-KOMPAS media to improve critical thinking skills and learning outcomes. This research uses the type of R&D with the ADDIE model with five stages. The feasibility of E-KOMPAS is measured by using validation tests by material and media experts. The effectiveness of E-KOMPAS media is measured by t-test between pretest and posttest. Meanwhile, the practicality of E-KOMPAS media uses teacher and student response questionnaires. Product feasibility tests by material experts obtained an average value of 98% with a very feasible category and feasibility by media experts obtained 97.3% with a very feasible category. The level of practicality obtained an average of 95% with a very practical category. Then in the t-test known sig. (2-tailed) of 0.000 which means there is a difference between pretest and posttest. The results of research and development of E-KOMPAS media are declared feasible, effective, and practical to improve critical thinking skills and learning outcomes of grade IV elementary school students.